THE EFFECTIVENESS OF USING HARVESTING MACHINES (COMBINE HARVESTER) IN RICE HARVESTING IN BOJONEGORO REGENCY - Badiatud Durroh (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
Rice harvesting in Indonesia is currently still dominated by human labor using a very high workforce, approximately 40% of the use of labor for intensive rice. Besides labor problems, cultural problems are also caused by the high loss of rice harvest in the paddy fields, where the postharvest shrinkage rate is 20%. The study was conducted in the Bojonegoro district in 2019, which was represented by several regions as samples, which were selected by cluster sampling based on sub-districts. This research uses a combination of Analytical Survey Method and Descriptive Survey Method. The results showed that the effectiveness of using the highest rice harvester in Bojonegoro Regency was 58%. Based on the ratio of the effectiveness of production to the effectiveness of using a combined rice harvester, the percentage is above 100% and is categorized as less effective. This is because the performance of the Combine Harvester tool is greatly influenced by the condition of the land at harvest, which at harvest time conditions of waterlogged land greatly affect the movement of tools on the land and the speed of the tool at harvest due to muddy soil conditions can make the speed and movement relatively slow tool. The impact of the use of combining technology on community income in Bojojnegoro Regency was 14,600,000 rupiah/ha (36.04%) with R / C criteria 1, then the farming experienced benefits because the revenue was greater than the expenditure. It is hoped that the government will continue to strive for the equalization of rice harvester combine harvester machines because this technology can increase the income of farmers.